Sistem Monitoring Cairan Infus Berbasis IoT Menggunakan Protokol MQTT - Nur Afiyat; Raizly Helmi Navilla; Mohamad Hariyadi (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2023)
One of the medical equipment that is often used in hospitals is infusion; however, the infusion monitoring system is generally still manual so that medical staff must constantly monitor the infusion device condition, which is requiring more effort and time. In this study, a 500 ml Ringer’s lactate infusion fluid monitoring system was developed based on the internet of things (IoT) using the message queuing telemetry transport (MQTT) communication protocol and an IoT cloud server system using the MQTT Dash. This infusion fluid was chosen as it is the most widely used infusion fluid. The HX711 load cell was used as a sensor to determine the weight of the infusion fluid. In addition, the NodeMCU ESP8266 microcontroller was used since it is equipped with a WiFi module called the ESP8266 module, hence it can support the implementation of IoT systems. The MQTT protocol was used to send the data to users. It was then connected to the MQTT Dash application as a monitoring medium for medical personnel. The system’s performance based on the performance of the HX711 load cell sensor in terms of the accuracy of reading the weight of infusion fluids was very good. It is evidenced by the average error percentage value of 0.08% to 0.64%, meaning that load cell sensor works well as it remains within the error tolerance limit of 5%. Meanwhile, the quality of service (QoS) test revealed that the results of the average delay on all systems ranged from 0.014 ms to 0.023 ms. According to the telecommunications and internet protocol harmonization over networks (TIPHON) standards, these values are considered very good. After that, the average of packet loss testing results on all systems were 0% to 0.01%. According to the TIPHON standards, these values are likewise classified as very good.